SEROPREVALENCIA DE Toxoplasma gondii EN LLAMAS DE UNA EMPRESA PECUARIA EN MELGAR, PUNO - Saravia P., Marco (2004)
The objective of the present study was to determine the seroprevalence of Toxoplasma gondii in adult female llamas in two flocks of the Rural Alliance farm in the province of Melgar, Puno. A total of 157 blood samples were collected and analyzed using the indirect immunofluorescence test. The results indicated that 10.2 ± 4.7% (16/ 157) of llamas had antibodies against T. gondii. One flock had 13.3 ± 9.8% (6/45) seroprevalence and the other one had 8.9 ± 5.3% (10/112); however, no significant statistical differences were found between flocks or age groups. The results showed a relatively low seroprevalence to T. gondii in relation to other studies in the country.